Perilaku Konsumtif dan Gaya Hidup Hedonis Relasinya terhadap Minat Mahasiswa Menggunakan E-Commerce - Hayati, Hafizni Nur; Hidayati, Mareta Dwi; ‘Aini, Nadhirotul (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2024)
Technological developments have an impact on changing people's lives. Hedonistic and consumptive lifestyles are variables that affect the high interest in using e-commerce. Students tend to behave consumpively to fulfill their hedonistic lives, this is done by utilizing e-commerce platforms. Students' consumptive behavior is related to fashion products which are always the main concern. This research was conducted to determine the relationship between consumptive behavior and hedonistic lifestyle to interest in using shopee e-commerce. The object of this research is students of the Faculty of Sharia and Islamic Economics, Mathali'ul Falah Pati Islamic Boarding School Institute with a sample of 77 students selected using the purposive sampling technique. Data analysis using Smart-PLS software. The results of this study concluded that students' consumptive behavior and hedonistic lifestyle had no effect on their interest in using shopee e-commerce.